Comparative Phonetic-Acoustic Analysis Before and After Speech Therapy of Voices Suffering from Recurrens Paresis - Lauritzen, Kai; Frøkjær-Jensen, Børge (Annual Report of the Institute of Phonetics University of Copenhagen, 1970)
No abstract